Reposisi Teungku Dayah Sebagai Civil Society di Aceh - Nirzalin Nirzalin (Media Syari'ah, 2012)
The stage of socio-political history of Aceh notes that the existence of teungku dayah as civil society very prominent and decisive. In fact, the capacity of a qualified discourse and political independent has managed to become energy for teungku dayah in urging the state elite to put the interest of the people as a starting point for the development of various policy. But into the middle of the new order era to the post new order era their political authority crisis in Aceh. It also implies a weakening of their role as civil society. But their role as civil society is needed because various mal practice of power by state elite such as bribery, corruption, and collusion growing and sustainable. While other civil society such as NGO and academics has not taken root in community so that they can not be expected. This article explores how the concept of civil society and why the importance of repositioning teungku dayah as a force of civil society in Aceh.